Estudo químico e avaliação do potencial biológico da raiz de Kielmeyera coriacea Mart. & Zucc (Calophyllaceae) - (:unkn) unknown (Universidade Federal de Goiás, 2017)
Cerrado is a region whose biological richness is unique, being formed by about 10 thousand plants. The flora study, ethnobotanic stands out for understanding of the interaction of society whit plants. In this view, teacher Dr. Vanessa Pasqualotto research group’s has been carrying out ethnobotanic survey in collaboration with the Coqueiros community, with the objective of recovering and valuing the popular knowledge about medicinal plants, among which the Kielmeyera coriacea species, the focus of this study, stands out. In this group, 37 members were interviewed, of which 76% indicate K. coriacea for the treatment of infections, rheumatism, leukemia, tooth pain, among others. Thus, the chemical study of ethanolic extract of roots (EER) of this species, aiming at to characterize its secondary metabolites, since there are no chemical reports in the literature for this part of the plant. In addition antioxidant, antimicrobial and antitumor potential of K. coriacea were evaluated. From the liquid-liquid extraction of EER the hexane (FH), ethyl acetate (FAE) and hydroalcoholic (FHA) fractions were obtained; by the fractionation of FAE, the substance 3-hydroxy-2,4- dimethoxyxanthone was isolated. Additionally, a fingerprint study was performed by LC-MS technique, identifying major compounds such as δ-tocotrienol, prenylated acylphoroglucinol, 2-hydroxy-1-methoxyxanthone, quercitrin. EER, FH, FAE, FHA, its subfractions and the isolated substance were submitted to biological tests. FHA presented antioxidant action with EC50 de 201,53 μg mL-1. EER and FH-10 subfraction from FH fractionation, inhibited the bacterial growth of Streptococcus pyogenes and S. pneumoniae (Minimum Inhibitory Concentration of 6.25 and 1.56 μg mL-1, respectively); EER also inhibited the fungus Candida glabrata in 7.81 μg mL-1. Finally, FH, FAE and FH-10 presented an antitumor effect against the HeLa cells, which are related to cervical cancer (IC50 of 2.5 μg mL-1, 2.5 μg mL-1 and 0.89 μg mL-1, respectively). When correlating the chemical and biological data, it is possible that the FAE-4.7.3 subfractions, from the fractionation of FAE, and FH-10 are constituted by substances such as 4-hydroxy-2,3-methylenedioxy xanthone, 3-hydroxy-1,2-dimethoxy xanthone, lupeol, prenylated acylphoroglucinol and quercitrin, which could be associated with the biological potential found. Therefore, the knowledge acquired in this study contributed to the expansion of the chemical-biological knowledge of K. coriacea.
Chemical study and evaluation biological potential of the root of Kielmeyera coriacea Mart. & Zucc (Calophyllaceae)
Keywords: Kielmeyera coriacea; Xantona; Potencial biológico; Xanthone; Biologic potential; CIENCIAS EXATAS E DA TERRA::QUIMICA